VD_FINDINFO Décision / 2010 / 38 vom 5. März 2010 - VD Tribunal cantonal (2010)
CONDITION DE RECEVABILITÉ, RADIATION DU RÔLE, MOTIVATION DE LA DEMANDE | 61 let. b LPGA, 27 al. 5 LPA-VD, 79 al. 1 LPA-VD